DINAMIKA EMOSI ANAK BERKEBUTUHAN KHUSUS DI SEKOLAH INKLUSI : STUDI KASUS PADA SISWA TUNALARAS - Siti Fadilah; Yahdini Firda Nadirah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This research aims to understand the emotional dynamics of students with hearing impairments in the context of inclusive education at Special Elementary School (SKH) N 01 Serang City. With a qualitative approach and case study design, this research involved observations and interviews with students and teachers. Findings show that students with hearing impairments often face difficulties in managing and expressing emotions, which leads to aggressive behavior and withdrawal tendencies. However, through consistent support from teachers and implementation of a fun learning approach, students demonstrate progress in social and emotional skills. Parental involvement is critical to ensuring consistency in support strategies at home and school. This research emphasizes the need for a responsive and collaborative approach in inclusive education, so that students with hearing impairments can face emotional challenges and develop in an inclusive environment.